InfiniBand Network Architecture - Shanley, Tom (Addison-Wesley Professional, 2002)
InfiniBand is a new networking specification that revolutionizes the interconnect between processor and IO subsystems in the datacenter environment. InfiniBand delivers better performance, flexibility, and scalability than alternative network architectures. Copper wire and fiber optic InfiniBand links offer data rates ranging from 2.5 Gb/s to 30 Gb/s. This technology easily surpasses the performance of competing network infrastructures by providing kernel bypass and memory-to-memory transfer capabilities. InfiniBand Network Architecture is a comprehensive guide to InfiniBand technology. It describes all hardware and software operational aspects of InfiniBand networking. Using the same building-block approach found in all of the books in the PC System Architecture Series, this book details important concepts relating to the design and implementation of data networks using this emerging standard. A broad overview of the InfiniBand specification is provided, as well as detailed descriptions of all the architecture's operational characteristics. Specific topics of interest include: Packet addressing, channel adapters, and the role of switches, routers, and repeaters Queue Pair (QP) creation and operation Transfer types, including connected, datagram, and raw datagram service Send/receive operations, such as Send, RDMA Read and Write, and atomic Read/Modify/Write (RMW) operations Link and physical layer descriptions Subnet-local and global addressing The Subnet Manager (SM) and the Subnet Administrator (SA) Performance, communication, device, and baseboard managers Created for hardware and software engineers and developers, InfiniBand Network Architecture is a critical resource for understanding and implementing this revolutionary technology. 0321117654B11042002.